Ukraine after Maidan : revisiting domestic and regional security - Stępniewski, Tomasz; Soroka, George (Stuttgart : Ibidem-Verlag, 2018)
When public protests first began in Ukraine at the end of 2013, the failed promise of the Orange Revolution was still fresh in the minds of many Ukrainians. However, unlike in the aftermath of 2004-2005, the political and military crises ignited by the Euromaidan brought profound changes not only for Ukraine, but also for neighboring states and Europe more generally, calling into question the durability of the post-Cold War world order. Writing from a variety of viewpoints and backgrounds, this volume's contributors offer sustained analysis of how its legacies have reverberated throughout the postcommunist region and wider Europe.
Introduction : Ukraine in Fragile Security Contexts / Tomasz Stępniewski and George Soroka -- The Juiciest Fruit Left on the Vine : Ukraine as a Bargaining Failure / Yuval Weber -- The Ukraine Crisis, NATO, and Eastern Europeʹs Grey Zone of Security / Tomasz Stępniewski -- The Ukraine Crisis and Ontological (In)Security : Implications from a Finnish Perspective / Jussi Laine -- Assessing Domestic Security Challenges in Post-Maidan Ukraine : Two Critical Dimensions / George Soroka -- Western Leverage, Russiaʹs Resistance and the Breakdown of the Yanukovych Regime / Yuriy Matsiyevsky -- On Ukraineʼs Geopolitical Identity : Public Opinion Dynamics on NATO Accession in the Aftermath of the War with Russia / Joanna Fomina -- Demography and Migration as Determinants of Ukrainian Policy in the Context of State Security / Andrzej Szabaciuk -- Notes on Contributors.
Includes bibliographical references.
Online resource; title from PDF title page (EBSCO, viewed April 17, 2019).
English
eBooks on EBSCOhost
Keywords: Ukraine -- Politics and government -- 1991-2014.; Ukraine -- History -- Revolution of Dignity, 2013-2014.; Nationalism -- Ukraine -- History -- 21st century; Political violence -- Ukraine -- History -- 21st century; Ukraine -- Politique et gouvernement -- 1991-2014.; Ukraine -- Histoire -- 2013-2014 (Révolution de la dignité); Nationalisme -- Ukraine -- Histoire -- 21e siècle.; Violence politique -- Ukraine -- Histoire -- 21e siècle.; HISTORY -- Europe -- Western; Nationalism; Political violence; Politics and government; Ukraine; Since 1991; Political Science / World; History